Financing Business Entities Through Crowdfunding as an Alternative to Financing with Bank Products in 2020-2023 - Rybacka, Justyna (Journal of Finance and Financial Law, 2025)
The purpose of the article. This article is based on a study which aimed to determine whether crowdfunding had become a viable alternative to banking products for Polish companies between 2020 and 2023. It was important to verify the awareness of, and knowledge about, alternative forms of financing among organisations operating in Poland. The article therefore examines whether crowdfunding became an alternative to traditional sources of financing for small and medium-sized enterprises (SMEs) in Poland between 2020 and 2023. The following hypotheses were therefore put forward: H1: Start-ups were the entities that most frequently used crowdfunding between 2020 and 2023. H2: Entities that did not receive financing from a banking institution during this period considered crowdfunding to be an alternative way of raising capital. Methodology. The article presents the results of an empirical study aimed at determining the use of crowdfunding in Poland as a means of financing small and medium-sized enterprises between 2020 and 2023. It was also important to verify the methods used by the study participants to finance investments and current operations. The article uses a research methodology that includes the critical analysis of secondary sources, as well as methods such as analysis, synthesis, description, deduction, induction and reduction. Additionally, both Polish and foreign literature on corporate finance were analysed. Laws, resolutions, regulations, the scientific works of other organisations and reports were also examined to provide valuable information on crowdfunding in the 2020–2023 period. The generalising-synthesising method (deduction, reduction and induction) was employed to formulate recommendations. The inductive method was used to analyse the importance and characteristics of various sources of crowdfunding for enterprises. Conversely, the deductive method was employed to analyse the issue by starting from the macroeconomic situation in Poland and delving into the situations of enterprises and changes in the way they finance their activities. A reduction technique was used to perform a critical analysis of the literature and verify the formulated hypotheses. Results of the research. A quantitative survey of 150 businesses showed that, between 2020 and 2023, a small percentage of respondents used crowdfunding. This figure was around 10%. Entities that have opted for this method of financing are primarily start-ups, which are defined as companies that have innovative technologies and/or business models and are striving for significant growth in terms of both employees and sales (Kollmann et al., 2015, p. 15). The study showed that, between 2020 and 2023, crowdfunding in Poland was mainly used by organisations from the IT, medical, cosmetics, and culture and arts industries. It is also important to note that awareness of this form of financing was relatively low during the analysed period. Only 20% of the entities surveyed found it interesting, while 24% had no opinion on the subject and 56% were unaware of it. The survey results showed that Polish entrepreneurs mainly identify the following forms of business financing: bank credit, own funds and capital borrowed from family or related parties.